PUBLIC-PRIVATE PARTNERSHIPS IN THE FIELD OF VOCATIONAL EDUCATION AND TRAINING IN THE EUROPEAN UNION: CURRENT TRENDS (Innovative professional education, 2023)
This article discusses the trends in public-private partnerships for vocational education and training in the European Union (EU). It outlines the content of public-private partnership programs, which focus on improving the quality and accessibility of vocational education and training, promoting innovation, financing training  programs, and fostering cooperation between educational institutions, public, private, and non-profit organizations. The article provides recommendations for utilizing progressive ideas from the EU's experience to develop public-private partnerships for vocational education and training in Ukraine.
Keywords: public-private partnership, vocational education and training, trends, European Union, programs, projects